Repositioning in value chain for smart city ecosystems: A viable strategy for historical telecom actors - Amirhossein Ghanbari; Oscar Álvarez San-Jaime; Thomas Casey; Jan Markendahl (International Telecommunications Society (ITS), 2015)
In a historical business model, Mobile Network operators (MNO) design their own network, own their infrastructure, operate the network and offer services on top of it; a voice-revenue dependent business. Now with the data provisioning, since the revenues associated with data do not comply with the pattern of increasing data usage in mobile networks, MNOs need new revenue streams. As a result, MNOs have started changing their business models by offering services besides their usual competences. This complicated approach has then forced them to think of possible cooperation patterns in order to benefit from horizontal collaboration with others, instead of being vertically integrated. On the Other hand, Telecom Equipment Vendors (TEV) used to design their business models in a vertical manner as well. TEVs would build and manufacture equipment and sell them to their customers in a Business-to-Business (B2B) fashion while in some cases operate the networks on behalf of their customers. Looking for new markets and revenue streams, the future Smart Cities comprise a good opportunity for MNOs and TEVs. This opportunity then requires a new mindset among these actors. In the new mindset, these actors should accept to reposition themselves in the new value chain. This means that, in order to play a role that can not be overlooked, MNOs and TEVs should perform rather different blocks of the Smart City value chain. This paper intends to provide an analysis of how the traditional telecom actors (MNOs and TEVs) have changed their business strategy and repositioned in the context of the Smart City service provision. In order to do that, we will introduce the traditional telecom actors and the existing value chain, later on, smart city concept and use cases will be introduced, finalizing with an analysis of how the future smart city value chain and the repositioning of these actors.
Keywords: 330; Business Model; Horizontalization; Repositioning; Value Chain; Smart City; Telecom Actor